CREATION OF CONDITIONS FOR ORGANIZATION OF LEISURE AND PROVISION OF RESIDENTS WITH SERVICES IN THE SPHERE OF CULTURE IN MOSCOW CITY - N. Musinova (Вестник университета, 2019)
The concept of “creating conditions for the organization of leisure and providing residents with the services of the sphere of culture” has been revealed. The features of the organization of management of cultural and leisure sphere in the city of Federal significance – Moscow have been considered. The creation of conditions for the organization of leisure of citizens and their provision with services of the sphere of culture has been analyzed. The most significant shortcomings, hindering the further development of cultural and leisure activities in the city of Moscow have been named and the main directions of its further development have been determined.